(untitled) (Interdisciplinary Studies Journal, 2025)
Mental health is profoundly influenced by the environments in which people live, and its promotion requires integrated actions across various sectors, including government. To analyze the functioning of multilevel governance in the Mental Health Policy Network of the State of Amazonas from the perspective of health workers, deepening the understanding of this governance model. The study adopted a qualitative and descriptive approach to investigate multilevel governance in the mental health policy of Amazonas. Using techniques such as questionnaires and systematic observations, the analysis was grounded in understanding institutional arrangements and identifying gaps in health networks. The research was conducted in Mental Health Units of the Psychosocial Care Network (RAPS) across 24 municipalities. The analysis revealed significant challenges in coordinating and implementing mental health services in Amazonas. Collaboration between different levels of government and civil society is essential to overcome historical barriers that undermine policy effectiveness. It is crucial to strengthen inter-institutional articulation and invest in professional training, adapting policies to local realities. Adequate funding and the implementation of continuous monitoring systems are essential to expand and improve service quality. The analysis of multilevel governance in the mental health policy of Amazonas highlights significant challenges in coordinating and implementing services. It is recommended to reinforce inter-institutional collaboration, invest in professional training, and ensure adequate funding. The approach should be adapted to regional particularities, with continuous policy monitoring. Future studies on digital technologies and the geography of Amazonas are essential to improve access to mental health services in remote areas.